Business Space Arrangement of Batik Iket Product Display For Permai Indonesia Participants in Pinang Malaysia - Harahap, Rachmita Maun; Suriastuti, Mira Zulia (Jurnal Abdi Masyarakat (JAM), 2025)
Workshop for Permai business actors in Penang, Malaysia on the arrangement of product displays for Batik Iket Celup. The goal of this workshop is to support traditional batik production's business development initiatives, particularly those related to Batik Iket.  Offering goods displays, including open, shut, inside, nameplate, and product decorating, as well as delear and external displays, this layout configuration allows for an interior display of Batik Iket products.In order to increase the capacity of business players in the designing of Batik Iket product displays, this goal is accomplished via the employment of a workshop method that emphasizes cooperation and consultation.  This workshop activity is expected to produce a process that helps business actors become more efficient in their present and future jobs by developing of appropriate habits of thought, action, skills, knowledge and attitudes. The result of this PKM will provide scientific insights both presentations and training on the process of making dyed Batik Iket.